2015
DOI: 10.1515/amm-2015-0413
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Continuous Casting Forms on the Shape of the Solidified Crust / Wpływ Geometrii Formy Na Kształt Frontu Krzepnięcia Przy Odlewaniu Ciągłym

Abstract: WpłyW geometrii formy na kształt frontu krzepnięcia przy odleWaniu ciągłymAn analytical model for the transfer has been development and applied for calculating the shape of the solid thickness profile for continuous casting of a thin plate as an example. The stationary solidification front relative to the crystallizer was received from the superposition of the motions of the liquid metal flow in the axial direction and the solidifying metal in the perpendicular direction. The shape of the solidified crust was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The slow crystallization caused by the slow movement of the ingots into the crystallizer promotes liquid phase dissolution and solid phase diffusion of these deposits, which affects the formation of finer particles with a size of 1-5 μm and less than 1 μm. This can be explained by similarly observed changes in the structure of brass ingots exposed to the magnetic field [3] or other impacts [2,4,5,11,12] affecting the formation of dendrites. The analyzes also showed that the refining process reduces the number of non-metallic inclusions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The slow crystallization caused by the slow movement of the ingots into the crystallizer promotes liquid phase dissolution and solid phase diffusion of these deposits, which affects the formation of finer particles with a size of 1-5 μm and less than 1 μm. This can be explained by similarly observed changes in the structure of brass ingots exposed to the magnetic field [3] or other impacts [2,4,5,11,12] affecting the formation of dendrites. The analyzes also showed that the refining process reduces the number of non-metallic inclusions.…”
Section: Discussionmentioning
confidence: 85%
“…Determination of process parameters refers to the formation of a liquid and solid phase separation layer [5 -7]. The use of waste materials results in distortion of this layer, which in turn does not allow for the adoption of already known models [8][9][10][11][12]. The problem is particularly exaggerated when raw materials are of quite different composition [13][14][15].…”
Section: Introductionmentioning
confidence: 99%